2011
DOI: 10.1186/1477-3155-9-35
|View full text |Cite
|
Sign up to set email alerts
|

Tubular immunostimulating complex based on cucumarioside A2-2 and monogalactosyldiacylglycerol from marine macrophytes

Abstract: Background: There is an urgent need to develop safe and effective adjuvants for the new generation of subunit vaccines. We developed the tubular immunostimulating complex (TI-complex) as a new nanoparticulate antigen delivery system. The morphology and composition of TI-complexes principally differ from the known vesicular immunostimulating complexes (ISCOMs). However, methodology for the preparation of TI-complexes has suffered a number of shortcomings. The aim of the present work was to obtain an antigen car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The absence of the similar effect of MGDGs on immune response against HA0 s of influenza A virus and porin of Y. pseudotuberculosis [Sanina et al, 2012] suggests that the immune response is dependent not only on the components of the TI-complex and their ratio [Kostetsky et al, 2011] but the particular structure of the antigen in the content of this promising nanoparticulate adjuvant delivery system.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The absence of the similar effect of MGDGs on immune response against HA0 s of influenza A virus and porin of Y. pseudotuberculosis [Sanina et al, 2012] suggests that the immune response is dependent not only on the components of the TI-complex and their ratio [Kostetsky et al, 2011] but the particular structure of the antigen in the content of this promising nanoparticulate adjuvant delivery system.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier, we showed that TI-complexes provide higher adjuvant effect in comparison with ISCOMs, liposomes or Freund's complete adjuvant [Kostetsky et al, 2011].…”
mentioning
confidence: 99%
“…The cucumarioside A 2 -2 -cholesterol -MGalDG ratio of 6:2:4 (by weight) was found to provide the most effective formation of TI-complexes and the minimum hemolytic Toxinology DOI 10.1007/978-94-007-6650-1_3-1 # Springer Science+Business Media Dordrecht 2014 activity in vitro. The TI-complex was able to increase the immunogenicity of the protein antigens from Yersinia pseudotuberculosis by three to four times (Kostetsky et al 2011).…”
Section: Immunostimulating Complexesmentioning
confidence: 99%
“…ISCOMATRIX is a flexible structure, which allows replacing their main components on structure-related compounds [ 5 ]. Therefore principally new biologically active, well-characterized components, glycoglycerolipids and saponins from marine hydrobionts, were proposed to modify and optimize ISCOMATRIX vehicles for microbial antigens [ 12 ].…”
Section: Elaboration Of Tubular Immunostimulating Complexmentioning
confidence: 99%
“…The present review summarizes literature data on properties of TI-complexes. These complexes consisting of lipid, cholesterol, and saponin [ 5 ] like their prototype, matrix of immunostimulating complex (ISCOMATRIX®) [ 3 ], are the most promising nanoparticulate adjuvant systems for the creation of effective and safe vaccines. In the present review, we discuss results published in series of our articles on elaboration, qualitative and quantitative composition, ultrastructure, and immunostimulating activity of TI-complexes.…”
Section: Introductionmentioning
confidence: 99%